The Determinants of Capital structure: Evidence from the Real Estate Industry and the Electronic and Electrical Equipment Industry listed on the SSE - YANG, YUCHUN (2017)
This paper aims to analyze the determinants of capital structure among the real estate industry and the electronic and electrical equipment (EEE) industry. All the firms are listed on the Shanghai Stock Exchange (SSE) and the data of firms are collected in the DataStream. Using the panel data model to analyze data over the period between 2007 and 2016, it finds that there are some differences of empirical results between those two industries. For the real estate industry, leverage increases along with the rise of size, growth and non-debt tax shields, but the association among profitability, tangibility, volatility and total leverage is negative. With regard to the EEE industry, size, growth and tangibility have positive association with leverage while profitability, non-debt tax shields and volatility are negatively relevant to leverage. Moreover, the determinants of the real estate industry and the EEE industry also have differences. The determinants of the real estate firms are size, growth, non-debt tax shields and volatility. However, in the EEE industry, the capital structure determinants are size, profitability and growth. This paper also has compared the empirical results of two industries with the whole market listed on the SSE. It turns out that the determinants of a specific industry and the whole market are different. The different results indicate that the firm’s capital structure determinants are different from each other. Since the firms may have various determinants, managers need to analyze the financing conditions and to find the accurate determinants of capital structure for the firms.